'It's like being pushed into sea on a boat with no oars': Breast cancer survivorship and rehabilitation support in Ireland and the UK. Issue 2 (8th December 2022) - Deery, Elizabeth; Johnston, Katie; Butler, Thomas
Abstract: Background: Cancer survivorship is associated with co‐morbidities including anxiety, depression and cardiovascular disease (CVD). Rehabilitative care post‐treatment is vital for survivors' psychological and physical well‐being. The present study aimed to investigate breast cancer survivors' attitudes towards their health post‐treatment; their awareness of co‐morbidities associated with treatment; and their awareness of support systems available. Methods: A qualitative research approach was employed, using semi‐structured interviews with breast cancer survivors from the UK and Ireland. Data were analysed using thematic analysis. Eight breast cancer survivors were recruited through purposive sampling. Results: Two themes emerged from the data: (1) health and rehabilitation post‐treatment, which included mental and physical health and a desire to control one's own health in survivorship as well as a discussion around co‐morbidities, and (2) access to support services in survivorship, which highlighted both positive and negative experiences of accessing support, as well as reasons for not accessing support in survivorship. Conclusions: Access to rehabilitation support, including diet, exercise and stress management, is key to survivorship. Rehabilitation and support services need to be more readily available for survivors to aid them in this journey and to educate them on the increased risk of conditions such as CVD with cancer treatment. Utilising current cardiac rehabilitation models could be a solution to provide a holistic cancer rehabilitation, thus providing the lifelong support that cancer survivors both want and need. Abstract : Factors contributing to health and rehabilitation in breast cancer survivorship. Key points: Access to rehabilitation support, including diet, exercise and stress management, is key to survivorship; however, access to support differed and was lacking for many survivors. Longer‐term comorbidities of cancer treatment were not fully understood. Therefore, there is a need for rehabilitation and support services to educate survivors on the increased risk of conditions such as cardiovascular disease with cancer treatment. These services must also address long‐term risk through lifestyle factors, including diet and physical activity. Utilising current cardiac rehabilitation models could be a solution to provide a holistic cancer rehabilitation, thus providing the lifelong support that cancer survivors both want and need.